Preliminary assessment of a tidal test site on the Minho estuary. (October 2020) - Díaz, H.; Rodrigues, J.M.; Guedes Soares, C.
Abstract: A characterization of tidal parameters at estuaries and the potential of these to be used for tidal energy extraction is performed. The tidal parameters analysed are crossed with estuaries around the world to obtain a selection of potentially feasible locations. A case study is addressed regarding the preliminary evaluation of location and overall characteristics of a tidal test centre and tidal farm in the Minho River estuary at the border between Spain and Portugal. Technical and environmental requirements are analysed to evaluate the potential of the location. Infrastructure characteristics, electrical connections and other equipment specification are determined considering the potential capacity available in the estuary; alternative configurations are studied and compared. Based on the study, the maximum capacity of the tidal technology centre is taken into account to produce an initial estimate of costs to deploy a device. The feasibility study shows that the economic evaluation of the investment is favourable, and the development of this tidal test site is feasible and economically viable. Even, a private organism could develop this project without any type of direct public investment. Highlights: A characterization of tidal parameters at estuaries and their potential to be used for energy extraction is performed. A study regarding the evaluation of characteristics of a tidal test centre and tidal farm in the Minho estuary is addressed. Infrastructure characteristics, and required equipment are determined considering the potential available in the estuary. The capacity of the tidal technology centre is taken into account to produce an estimate of costs to deploy a device.